Multi-Tier Architecture Design for Scalable and Effective Non-Formal Learning: A Redesign of Serat Kartini Women's School LMS - Ardana, Primavieri Rhesa; Trisnapradika, Gustina Alfa (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
Non-formal education plays a vital role in empowering women in rural areas of Central Java, Indonesia. However, the existing Learning Management System (LMS) of Woman School Serat Kartini, built on a monolithic Laravel architecture, suffers from significant performance degradation and scalability limitations under growing user loads and shared hosting constraints. This leads to high latency, frequent session interruptions, and reduced participation, ultimately undermining learning effectiveness. This study redesigns the LMS using a multi-tier application architecture through the Design Science Research (DSR) methodology. The proposed blueprint separates the system into four independent tiers: Presentation (Next.js for users, React.js for administrators), Logic (Express.js for API Layer), Cache (Redis with cache-aside strategy), and Data (MySQL). The design artifacts include detailed architecture diagrams, ERD, use case, and sequence diagrams. Conceptual evaluation demonstrates that the multi-tier approach enhances modularity, reduces latency, supports horizontal scalability, and improves resource efficiency , ensuring reliable access for women learners with limited digital literacy and unstable internet connectivity. The redesigned LMS conceptually strengthens learning accessibility, engagement, and program sustainability in resource-constrained non-formal education contexts. This research is limited to the conceptual design phase without implementation or empirical testing.